Una estrategia de formación del profesorado basada en la metacognición y la reflexión colaborativa: el punto de vista de sus - Rodríguez Marcos, Ana; Gutiérrez Ruiz, Irene (Revista Española de Pedagogía, 2018)
The authors analyse a methodological strategy that starts from a treatment of the epistemological and didactic conceptions of pupils, that initiate the study of the subject General Didactic, to foster the acquisition of technical-practical knowledge and the development of skills, capabilities and attitudes needed for a reflective teaching. The results show that, in general, students judged positively this strategy.
A TEACHER EDUCATION STRATEGY BASED ON METACOGNITION AND COLLABORATIVE REFLECTION: THE PROTAGONISTS' POINT OF VIEW
Keywords: previous beliefs; collaborative reflection; small group; large group; metacognilion; self-esteem; Revista Española de Pedagogía